Effect of Geometrical arrangement on the electrical conductivity of some successive polymers (Para- polyamide - Meta polyamide) - Yousef Shehab; Haitham Al Wahab; Huda Al-Bakri (College of Education for Pure Sciences, 2005)
The para&mcta-poly amide were prepared by the condensation polymerization process of para- phenylenediamine and mela-phenylenediaiuine malic unhydride successively. 1 he electrical conductivity was studied for both by using an electrical cell made locally for this purpose, in addition to that (he effects of the physic properties of each polymer, which affects the electric conducthily have been studied. One of the most important properties of polymer is (lie Geometrical arrangement, which according to (he results that we have come to, was made clear the geometrical arrangement affects to a very great extent the electric conductivity of each polymer,